Perancangan sistem informasi user education berbasis Web: Best practice Perpustakaan IAIN Salatiga - Ifonilla Yenianti (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2021)
Islamic State Institute of Religious Affair (IAIN) Salatiga library carries out user education for new library members / new students on new student orientation. In the 2019/2020 academic year, and in 2021, IAIN Salatiga library cannot conduct user education face-to-face due to the Covid-19 pandemic. So the researcher and librarian of IAIN Salatiga tried to design a web-based user education information system. The purpose of this research is to design a web-based user education information system to make it easier for new students of IAIN Salatiga to follow user education online and without a time limit (unlimited) and at the same time register as a member of the IAIN Salatiga library online. This study uses a qualitative descriptive approach with the method of observation, interviews and literature study. The design method used is object-oriented through the Unified Modeling Language (UML) modeling stage, namely use case diagrams and class diagrams as database.